Dissecting Dynamic and Heterogeneous Proteasome Complexes Using In Vivo Cross-linking Assisted Affinity Purification and Mass Spectrometry - Wang, Xiaorong (Methods Mol Biol, 2018)
Protein-protein interactions are essential for protein complex formation and function. Affinity purification coupled with mass spectrometry (AP-MS) is the method of choice for studying protein–protein interactions at the systems level under different physiological conditions. Although effective in capturing stable protein interactions, transient, weak and or dynamic interactors are often lost due to extended procedures during conventional AP-MS experiments. To circumvent this problem, we have recently developed XAP (in vivo cross-linking (X) assisted Affinity Purification) MS strategy to better preserve dynamic protein complexes under native lysis conditions. In addition, we have developed XBAP (in vivo cross-linking (X) assisted Bimolecular tandem Affinity Purification) MS method by incorporating XAP with bimolecular affinity purification to define dynamic and heterogeneous protein subcomplexes. Here we describe general experimental protocols of XAP- and XBAP-MS to study dynamic protein complexes and their subcomplexes, respectively. Specifically, we present their applications in capturing and identifying proteasome dynamic interactors and ubiquitin receptor (UbR)-proteasome subcomplexes.